Quercetin attenuates tau hyperphosphorylation and improves cognitive disorder via suppression of ER stress in a manner dependent on AMPK pathway. (April 2016) - Chen, Junjun; Deng, Xueyang; Liu, Ning; Li, Min; Liu, Baolin; Fu, Qiang; Qu, Rong; Ma, Shiping
Highlights: ER stress/NLRP3 inflammasome activation was involved in tau protein phosphorylation-induced cognitive dysfunction. Quercetin inhibited ER stress which contributed to ROS generation and mitochondrial dysfunction. AMPK activation of quercetin attenuates tau protein phosphorylation. Quercetin-3-O-glucuronide exerts similar effects to quercetin in okadaic acid-induced neurodegenerative model. Abstract: Quercetin, a natural flavonoid abundantly found in onions, apples, tea, berries, cauliflower, and red wine, has been demonstrated to exert beneficial effect on Alzheimer's disease. We aimed to investigate its AMPK activity on hyperphosphorylation of tau and explore the underlying mechanism associated with Endoplasmic reticulum (ER) stress. Quercetin and quercetin-3-O-glucuronide suppressed ER stress with decreased phosphorylation of IRE1α and PERK, thereby inhibited TXNIP and NLRP3 inflammasome activation, ultimately attenuated tau phosphorylation in okadaic acid (OA) induced SH-SY5Y cells. However, the effect on tau phosphorylation was blocked by downregulation of AMPKα1/2 with SiRNA transfection. Moreover, administration of quercetin enhanced AMPK activity, inhibited IRE1α and PERK phosphorylation, NLRP3 expression and tau phosphorylation and improved cognitive disorder in mice exposed to high fat diets. AMPK may be a key player that links ER stress and tau phosphorylation and mediates quercetin's effect on cognitive disorder. Thus, quercetin and its AMPK activity may provide a potential therapeutic strategy for treatment of AD patients.